Comparative analysis of Arabidopsis UGT74 glucosyltransferases reveals a special role of UGT74C1 in glucosinolate biosynthesis. (13th June 2014) - Grubb, C. Douglas; Zipp, Brandon J.; Kopycki, Jakub; Schubert, Melvin; Quint, Marcel; Lim, Eng‐Kiat; Bowles, Dianna J.; Pedras, M. Soledade C.; Abel, Steffen
Summary The study of glucosinolates and their regulation has provided a powerful framework for the exploration of fundamental questions about the function, evolution, and ecological significance of plant natural products, but uncertainties about their metabolism remain. Previous work has identified one thiohydroximate S‐glucosyltransferase, UGT74B1, with an important role in the core pathway, but also made clear that this enzyme functions redundantly and cannot be the sole UDP‐glucose dependent glucosyltransferase (UGT) in glucosinolate synthesis. Here, we present the results of a nearly comprehensive in vitro activity screen of recombinant Arabidopsis Family 1 UGTs, which implicate other members of the UGT74 clade as candidate glucosinolate biosynthetic enzymes. Systematic genetic analysis of this clade indicates that UGT74C1 plays a special role in the synthesis of aliphatic glucosinolates, a conclusion strongly supported by phylogenetic and gene expression analyses. Finally, the ability of UGT74C1 to complement phenotypes and chemotypes of the ugt74b1‐2 knockout mutant and to express thiohydroximate UGT activity in planta provides conclusive evidence for UGT74C1 being an accessory enzyme in glucosinolate biosynthesis with a potential function during plant adaptation to environmental challenge.